O prontuário do paciente na perspectiva arquivística - Ciocca, Isabella Gelás [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The relevance of the records of patients, their production and guard bring concerns on how to keep them organized and accessible in archive. Considering the benefits of preventive conservation process applied to files, we cover and discuss the concepts and principles that can guide and educate users and responsible for collection. The advantages of this process, we emphasize that the lifting of the legislation and of the routines in this documentary production is necessary, because for the study of the applicability of preventive conservation, it is necessary to understand the whole flow of the documentary sector. The problem focused refers to the records of patients of the Center for the Study of Education and Health (CEES) at UNESP/Campus Marilia. The analysis of difficulties in search of the desired information, to better match the guard and the processes of access to these documents were guiding to assess the contributions of preventive conservation. Thus, we discussed about the production of documents and we present the definitions about the conservation of documents, providing greater knowledge about this process, and, so, we highlight the improvements in the guard and access to documentation.

A relevância dos prontuários dos pacientes, sua produção e guarda trazem preocupações em como mantê-los organizados e acessíveis em um arquivo. Considerando os benefícios resultantes do processo de conservação preventiva aplicado em arquivos, abordamos e discutimos os conceitos e princípios capazes de orientar e conscientizar os usuários e responsáveis pelo acervo. Das vantagens desse processo, destacamos que o levantamento da legislação e das rotinas dessa produção documental se faz necessário, pois para o estudo da aplicabilidade da conservação preventiva, é necessário compreender todo o fluxo documental do setor. O problema focado refere-se aos prontuários dos pacientes do Centro de Estudos da Educação e Saúde (CEES) da UNESP/Campus de Marília. A análise de dificuldades na busca pela informação desejada, a melhor adequação na guarda e os processos de acesso a esses documentos foram norteadores para avaliar as contribuições da conservação preventiva. Dessa forma, discutimos sobre a produção documental e apresentamos as definições a respeito da conservação documental, fornecendo maior conhecimento acerca deste processo, e, assim, destacamos as melhorias na guarda e acesso à documentação.
Keywords: Registros hospitalares; Registros médicos; Conservação preventiva; Documentos arquivísticos - Digitalização; Sistemas de recuperação da informação; Arquivologia; Hospital records